Formulation and Evaluation of Toothpaste Combining Clove Flower Extract (Syzygium aromaticum L.) and Chamomile Flower Essential Oil (Matricaria chamomilla) - Elmaria; Paramawidhita, Risqika Yuliatantri; Rika Arfiana Safitri (Crown: Journal of Dentistry and Health Research, 2024)
Introduction: Herbal remedies like clove and chamomile have been traditionally used for their potential oral health benefits. This study aimed to formulate and evaluate a toothpaste combining clove flower extract (Syzygium aromaticum L.) and chamomile flower essential oil (Matricaria chamomilla) for its efficacy in promoting oral hygiene. Methods: Clove flower extract was obtained through ethanol extraction, while chamomile essential oil was procured commercially. Various toothpaste formulations (F1-F3) were prepared with varying concentrations of the herbal extracts, alongside a control formulation (F0) without the extracts. The formulations underwent comprehensive evaluation, including organoleptic assessment, pH determination, homogeneity testing, and foam height analysis. Additionally, antimicrobial activity against common oral pathogens (Streptococcus mutans and Staphylococcus aureus) was assessed using the agar well diffusion method. Results: All formulations (F0-F3) exhibited acceptable organoleptic properties, pH levels within the safe range for oral use, and homogeneity. However, foam height varied among formulations, with F1-F3 showing lower foam compared to the control (F0). Notably, F2 and F3 demonstrated significant antimicrobial activity against both S. mutans and S. aureus, suggesting their potential in combating oral pathogens. Conclusion: The combination of clove flower extract and chamomile essential oil in toothpaste formulations holds promise for enhancing oral hygiene due to their antimicrobial properties. Further research is warranted to optimize foam height and explore the long-term clinical effects of this herbal toothpaste.